An unusual case of pulmonary embolism - Khakural, Prabhat (J Surg Case Rep, 2015)
Pulmonary embolism carries a significant morbidity and mortality. Metastatic choriocarcinoma presenting as pulmonary embolism is a rare event. Here, we report a case of a 25-year-lady with a history of worsening shortness of breath for 4 months who was treated as a case of pneumonia and tuberculosis. Owing to the worsening condition, she had a contrast enhanced computed tomography (CECT) chest done and was diagnosed to have pulmonary embolism. She underwent pulmonary embolectomy. The histopathological examination of the embolus revealed it to be metastatic choriocarcinoma. She showed a good response to chemotherapy. Metastatic choriocarcinoma should be considered as a differential diagnosis in females presenting with pulmonary embolism.